2006
DOI: 10.1136/gut.2006.093187
|View full text |Cite
|
Sign up to set email alerts
|

Control of matrix metalloproteinase production in human intestinal fibroblasts by interleukin 21

Abstract: Background: T cell-mediated immunity plays a central part in the pathogenesis of tissue damage in inflammatory bowel disease (IBD). The mechanism by which T cells mediate tissue damage during IBD remains unclear, but evidence indicates that T cell-derived cytokines stimulate fibroblasts to synthesise matrix metalloproteinases (MMPs), which then mediate mucosal degradation. We have previously shown that, in IBD, there is high production of interleukin (IL) 21, a T cell-derived cytokine, which enhances Th1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 36 publications
2
116
1
1
Order By: Relevance
“…The behaviour of C3 mRNA expression in the IBD mucosa was different from other factors described previously [4,45,46]. Elevation of C3 mRNA expression was observed not only in active IBD mucosa but also in infectious colitis, although many factors have been reported to be elevated specifically in IBD mucosa [4,[45][46][47]. This suggests that C3 biosynthesis may be dependent upon molecular mechanisms specific and non-specific for IBD, as complements are major factors in innate immune responses against a huge number of antigens.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…The behaviour of C3 mRNA expression in the IBD mucosa was different from other factors described previously [4,45,46]. Elevation of C3 mRNA expression was observed not only in active IBD mucosa but also in infectious colitis, although many factors have been reported to be elevated specifically in IBD mucosa [4,[45][46][47]. This suggests that C3 biosynthesis may be dependent upon molecular mechanisms specific and non-specific for IBD, as complements are major factors in innate immune responses against a huge number of antigens.…”
Section: Discussionmentioning
confidence: 39%
“…This suggests that C3 biosynthesis may be dependent upon molecular mechanisms specific and non-specific for IBD, as complements are major factors in innate immune responses against a huge number of antigens. An increasing number of studies have focused upon the role of Th17 cells in the pathogenesis of IBD [8,10,[12][13][14]47], due to its unique differentiation processes under the stimulus of transforming growth factor (TGF)-b and IL-6 [3][4][5][6][7][8][9][10][11]. Th17 cells develop from naive T lymphocytes through distinct pathways from classical Th1 and Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between MMPs and their inhibitors results during inflammation, implicating that inflammatory We have recently demonstrated that IL-21R is expressed by gut fibroblasts and that IL-21 stimulation results in the enhanced secretion of MMP-1, MMP-2, MMP-3, and MMP-9 but not tissue inhibitors of metalloproteinases. 49 Neutralization of IL-21 markedly reduces the amounts of MMPs released when fibroblasts are cultured with CD lamina propria mononuclear cell supernatants, confirming the role of IL-21 as mediator of the MMP-mediated tissue damage ( Figure 2 ). Interestingly, IL-21 does not affect the expression of MMPs at the transcriptional or post-transcriptional level, rather it acts by causing the release of intracellular stores of MMPs.…”
Section: Il-21 Contributes To Gut Damage By Enhancing the Secretion Omentioning
confidence: 49%
“…Soon after, a functional cloning approach identified a four-helix-bundle cytokine with structural relation to interleukin (Il)-2, Il-4 and Il-15 as the natural ligand to this receptor, naming the new entities Il-21 13 . The Il-21 receptor (Il-21R) is widely expressed, indicating a broad range of actions of Il-21 14,15 . Il-21/Il-21R regulates activation, proliferation and survival of both CD4 + T cells and B cells, and limits the differentiation of inducible Tregs and counteracts their suppressive properties on effector T cells 16 , both of which are involved in the pathogenesis of NMO and MS. Il-21 now has also been reported to contribute to the development of Th17 cells, and Th17 cells can produce Il-21, acting in an autocrine manner to amplify its own synthesis.…”
mentioning
confidence: 99%